If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 2) * 3 = 0 Reorder the terms: (2 + 5x) * 3 = 0 Reorder the terms for easier multiplication: 3(2 + 5x) = 0 (2 * 3 + 5x * 3) = 0 (6 + 15x) = 0 Solving 6 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 15x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 15x = 0 + -6 15x = 0 + -6 Combine like terms: 0 + -6 = -6 15x = -6 Divide each side by '15'. x = -0.4 Simplifying x = -0.4
| 1.5(x+8)=4.3+0.8x | | 10a-a= | | 18c-29c=151-30 | | 0.6x+1.5=-0.6(2x+5) | | 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 | | 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 |